Maisi Sasuduik: Restrengthening the Implementation of the Concept of al-Ba`ah in some Minangkabaunese Traditional Marriages - Busyro, Busyro; Asmara, Musda; Wadi, Fajrul; Manap, Norhoneydayatie Abdul; Tarihoran, Adlan Sanur (Institut Agama Islam Negeri Curup, 2024)
This article aims at restrengthening the implementation of the al-ba’ah concept in maisi sasuduik tradition of some Minangkabaunese marriage customs because some people think that this tradition is just a custom and has nothing to do with Islamic teachings. Maisi sasuduik is an obligation for a prospective groom before marriage. This research uses a qualitative approach by which the data were collected through interviews with several community figures and from relevant literature. The descriptive and inductive theories were used in analyzing the data. The results of the research showed that some people believe that this custom has nothing to do with Islamic teachings. The finding reveal that marriages are sometimes postponed and some are even annulled because the men do not agree to fulfill maisi sasuduik custom. According to the concept of al-ba’ah in Islam, a man must prepare a house for his wife to live in because he will take her there after marriage. For Minangkabaunese men, they are not required to prepare a house to live in before marriage because they will live in the wives’ house. Based on the concept of al-ba’ah, Maisi sasuduik describes a man’s al-ba’ah (ability) to perform a marriage. Therefore, the custom of maisi sasuduik is an implementation of Islamic teachings regarding the necessity of having an al-ba’ah before marriage.